A COMPARATIVE ASSESSMENT OF THE BIOCHEMICAL ANALYSIS OF THE COURSE OF NON-ALCOHOLIC FATTY LIVER DISEASE IN PATIENTS WITH COVID-19 - o’g’li, Zokirov VohidZoyit (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2022)
This article analyzes a special experiment on the parameters of pigment metabolism, cytolysis and cholestasis to assess the functional state of the liver in non-alcoholic fatty liver disease in middle-aged and elderly patients who underwent COVID-19. The study included a control group of patients who did not have COVID-19, an experimental group of patients diagnosed with COVID-19, a history (periodic abstinence from alcoholic beverages) was collected to rule out alcoholic fatty liver disease and isolated using a special CAGE examination. The conclusion was made on the basis of the PCR test COVID-19.